POLA KOMUNIKASI KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Firdausi, Ahmad Thoriq; S.Sos., M.Med.Kom., Putri Aisyiyah Rachma Dewi, (The Commercium, 2023)
This thesis discusses communication patterns in the leadership of female school principals in improving the quality of education. The research aims to understand how female school principals build effective communication patterns with team members and stakeholders to achieve the goals set in accordance with the school's vision and mission. The research method used is a case study with observation and interview techniques. The results show that female school principals who are effective in building good communication patterns can improve the quality of education in schools. Successful female school principals in building effective communication patterns are those who are able to build good relationships with team members and stakeholders, ensure smooth information flow, and facilitate participation and collaboration from all parties involved